Occurrence and patterns of extralaryngeal branching of the recurrent laryngeal nerve in Thai cadavers - Baramee, Phichaya; Viwatpinyo, Kittikun; Pattarasakulchai, Thienchai; Mahakkanukrauh, Pasuk (Biomedical Sciences and Clinical Medicine, 2024)
Background and objective The recurrent laryngeal nerve (RLN) supplies motor control to the intrinsic laryngeal muscles, which is crucial for phonation and upper airway regulation, and receiving sensation from the vocal cord and subglottic region. Due to its proximity to the thyroid gland, this nerve is injured frequently during thyroidectomy, which leads to vocal cord paralysis. Despite anatomical landmarks provided for identifying the RLN during surgery, postoperative damage to this nerve still occurs. Past studies suggest that the RLN might have extralaryngeal branches that were unidentifi ed and subsequently damaged. This study aimed to identify and classify the pattern of extralaryngeal branching of the RLN in the Thai population. Method Seventy five neck specimens were used to identify the RLN and its extralaryngeal branches within the inferoposterior area to the thyroid gland. The branching pattern was then classified according to the number of branches leading to the larynx, and the difference between the left and right side were calculated by the chi-square test. Result and conclusion Branching of the RLN can be classified into three major types and ten subtypes. An RLN with at least one branch seen outside the laryngeal area was found in 52 sides (69.33%) of specimens. Among this variation, about 30% had an RLN with two or three branches entering the larynx. No statistically significant difference in the number of each variation was found between the left and right side. These data should be useful for minimizing RLN injury and complications from thyroid surgery.